PENILAIAN KEWAJARAN HARGA SAHAM SEBAGAI PERTIMBANGAN INVESTASI DI BURSA EFEK INDONESIA - Singgih, Marmono (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2012)
Price earnings ratios (PER) is used to evaluate the fair value of stock.The reason is that PER could help the analysts to make judgement on importantvariables. This research is meant to determine whether PER could be used toevaluate the fair value of stock. This value is determined by growth rate of earning(GE) and systematic risk (Î²) capabilities to clarify PER change and whether thevaluation model could be used as security selection. The taken samples were 30(thirty) stocks of The Indonesian Stock Exchange. The result of the valuationmodel is simultaneously the growth rate of earning and systematic risk couldexplain the PER change about 26,6%. The classical assumption test describes thatthe cross-sectional regression is BLUE (Best Linear Unbiased Estimator). Thevaluation model is highly successfull to determine stock price change, but thismodel is much less successfull to select which one of the stock is bought or sold(security selection).Keywords: